Potensi Aktinomisetes Asal Tanah Perakaran Mangrove Segara Anakan Cilacap Sebagai Penghasil Antifungi Terhadap Yeast Patogen Candida albicans - Rifqi Aulia Akbar; Dini Ryandini; Dyah Fitri Kusharyati (Universitas Gadjah Mada, 2017)
Isolation of actinomycetes has been done from mangrove soil sample of Segara Anakan Cilacap. This research aimed to know the potency of actinomycetes as an antifungal producer, and to measure antifungal activity produced by actinomycetes based on diameter zone inhibition and to know the characteristic of the bioactive compound with Thin Layer Chromatography method. The result of the study has been isolated 24 actinomycetes isolates, 15 of them had potential as an antifungal producer, which inhibited the growth of Candida albicans. Period of fermentation significantly affected to the activity of the antifungal compound. The highest inhibitory zone was formed by an antifungal extract from actinomycetes C with a range zone 19.7 mm in length at 14th days fermentation, which was extracted with ethyl acetate solvent (1: 1 v / v). The characteristic of a bioactive compound of the actinomycetes C ha s a Rf value 0.5 in the solvent n-butanol, acetic acid and water (3: 2: 1 v / v / v).